The Moderating Role Of Auditor Reputation On The Influence Of Audit Fees And Corporate Financial Distress On Auditor Switching - Nuryasin, Fadli (Journal of Economics and Business (JECOMBI), 2025)
The purpose of this study was to determine the effect of audit fees and financial difficulties on auditor switching with auditor reputation as a moderating variable. The research method uses quantitative methods. The research design consists of a descriptive design and a causal design. The sampling technique uses purposive sampling with a total sample of 27 infrastructure, utilities & transportation sector companies registered on the IDX for 2020-2023, where the research sample data is 135 sample data. Data analysis used logistic regression analysis and moderated regression analysis (MRA) with the SPSS Version 23 program. Based on the results of data analysis, it is known that the Nagelkerke R Square value is 0.689. This shows that the variation in giving auditor switching can be explained by 68.9% by the audit fee variable, financial distress with the auditor's reputation as a moderating variable, while the rest is explained by other variables not examined. The results of testing the hypothesis, it is known that audit fees have a positive effect on auditor switching, financial distress has a positive effect on auditor switching, auditor reputation moderates (weakens) the effect of audit fees has a positive effect on auditor switching, and auditor reputation does not moderate the effect of financial distress on auditor switching.